2022
DOI: 10.2147/idr.s347089
|View full text |Cite
|
Sign up to set email alerts
|

Association of TyG Index with CT Features in Patients with Tuberculosis and Diabetes Mellitus

Abstract: Background:The purpose of this study was to investigate the association of the triglyceride glucose (TyG) index, a surrogate marker of insulin resistance (IR) with a high sensitivity of 96.5% and a specificity of 85.0% for the diagnosis of IR, with computed tomography (CT) features in patients with tuberculosis and diabetes mellitus. Methods: A total of 247 subjects were enrolled from July, 2020 to May, 2021. The basic clinical features and CT features were analyzed. In addition, multivariate logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Our previous study has described the inclusion and exclusion criteria. 2 In brief, inclusion criteria: age ≥18; antituberculosis therapy no more than one week before hospitalization; active TB. Exclusion criteria: using lipid-lower agents; active tuberculosis in this study should conform to at least one of the following standards: sputum or bronchial lavage fluid (BALF) smear positive, sputum or BALF bacterial culture positive, GeneXpert Mycobacterium tuberculosis/rifampicin resistance in sputum or BALF positive.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study has described the inclusion and exclusion criteria. 2 In brief, inclusion criteria: age ≥18; antituberculosis therapy no more than one week before hospitalization; active TB. Exclusion criteria: using lipid-lower agents; active tuberculosis in this study should conform to at least one of the following standards: sputum or bronchial lavage fluid (BALF) smear positive, sputum or BALF bacterial culture positive, GeneXpert Mycobacterium tuberculosis/rifampicin resistance in sputum or BALF positive.…”
Section: Methodsmentioning
confidence: 99%
“…1 Low body mass index (BMI), diabetes, and smoking could be the risk factors for TB, and previous reports have established a strong relationship between diabetes and TB. 2 , 3 Compared with TB only patients, patients with TB-DM are easier to have unfavorable treatment outcomes with a higher mortality rate. After screening 7043 articles and identifying 43 eligible studies, a study reported the prevalence of TB-DM patients in China: Northeast China (21.9%) among the four economic regions of China, followed by East Coast (8.3%), Western China (5.9%), and Central China (5.1%).…”
Section: Introductionmentioning
confidence: 99%